Experimental study on the use of Savonius combined blade rotors as wind turbines and hydrokinetic turbines - Sanusi, Arifin; Ut Jasron, Jahirwan; Syam, Sudirman (International Journal of Power Electronics and Drive Systems (IJPEDS), 2025)
Renewable energy development is increasingly important to anticipate the limited use of fossil energy and its impact on the environment. The Savonius turbine is a vertical axis turbine that can utilize flow from all directions with simple construction, so it has the potential to be developed as a wind turbine and hydrokinetic to generate electricity. This paper aims to conduct an experimental studied the same Savonius combined blade rotor as a wind turbine used in a wind tunnel and a hydrokinetic turbine in an irrigation channel. The experimental results show that the Savonius turbine can function well as a wind and hydrokinetic turbine. The Savonius combined blade turbine improves the performance of conventional Savonius blade turbines, including its use as a hydrokinetic turbine, which is affected by flow velocity. The performance of the Savonius turbine is indicated by the power coefficient Cp and torque coefficient (Ct) values based on the fluid flow velocity. At the same wind speed (4 m/s), the combined blades can increase the performance Cp by up to 11% compared to conventional blades. The use of the same combined blades tested as a hydrokinetic turbine resulted in an increase in Cp and a decrease in Ct with an increase in tip speed ratio (TSR).